THE HERMENEUTICAL APPROACH TO TRANSLATION - Stolze, Radegundis (Vertimo studijos, 2017)
Departing from the definition of translation as a personalized activity, the article discusses the problem of the understanding for translation purposes against the backdrop of hermeneutics. Comprehension is an ongoing process, guided by the hermeneutical circle of relevant knowledge and learning. Hermeneutical translation competence involves the readiness for self-critical reflection, the openness for constant learning, the ability to integrate new cognitive input, the courage for linguistic creativity, and an empathetic identification with the message.Translation via a hermeneutic approach implies great responsibility. We know that interpretation is somewhat subjective and incomplete, but readers assume that they receive the content of a translated text in as faithful a manner as possible. For this purpose the translator needs holistic dimensions of orientation in the text being presented. And for the translation as text production rhetorical aspects have to be observed. The task of translating is a complex integration of various dimensions.